Pengetahuan, Pelayanan, dan Sosialisasi Pajak Kendaraan Bermotor Terhadap Kepatuhan Wajib Pajak (Studi Kasus pada Kantor Samsat Depok II Cinere) - Stiani, Devi (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2023)
This study aims to determine the Effect of Knowledge, Service, and Socialization of Motor Vehicle Tax on Taxpayer Compliance. The population in this study was 178,535 taxpayers registered at the Cinere Samsat Depok II Office. The collection technique used is the accidental sampling method with the calculation of sampling using the Slovin Formula, so that the sample obtained is as many as 100 taxpayer respondents. Data collection method using questionnaires analyzed using SPSS program version 27. Based on the results of the Coefficient of Determination test, an Adjusted R-Square value of 0.402 was obtained. The results of testing the Simultaneous Test hypothesis (Test f) show that Knowledge, Service, and Socialization of Motor Vehicle Tax simultaneously affect Taxpayer Compliance, this is proven that the three variables have a significance value level of 0.000 and obtained fcalculate of 23.217 where the fcalculate value is greater than the ftable value (23.217 > 2.70). The results of testing the partial test hypothesis (Test t) show that each independent variable has an influence on the dependent variable, where each of these variables has a significance value of less than <0.05 and obtains a tcalculate value greater than ttable >1.984.